2017
DOI: 10.24839/2325-7342.jn22.3.220
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Mood on Writing Apprehension, Writing Self-Efficacy, and Writing Performance

Abstract: ABOUT PSI CHI Psi Chi is the International Honor So ci ety in Psychology, found ed in 1929. Its mission: "recognizing and promoting excellence in the science and application of psy chol ogy." (Note. Our new mission statement is available at http://www.psichi.org/?page=purpose) Mem ber ship is open to undergraduates, graduate students, faculty, and alumni mak ing the study of psy chol ogy one of their major interests and who meet Psi Chi's min i mum qual i fi ca tions. Psi Chi is a member of the As so cia tion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Many researchers found that one of the primary reasons causing writing anxiety is a lack of writing practice throughout an academic career (Rabadi and Rabadi, 2020). Effective aspects such as aversion to writing, fear of criticism, and anxiety of being judged were also reported among anxious writers (Cheng et al, 1999;Vanhille et al, 2017;Rabadi and Rabadi, 2020). Meanwhile, individual differences such as age, gender, and socioeconomic background have been linked to various writing anxiety levels (Huwari and Abd Aziz, 2011).…”
Section: Factors Causing Writing Anxietymentioning
confidence: 99%
“…Many researchers found that one of the primary reasons causing writing anxiety is a lack of writing practice throughout an academic career (Rabadi and Rabadi, 2020). Effective aspects such as aversion to writing, fear of criticism, and anxiety of being judged were also reported among anxious writers (Cheng et al, 1999;Vanhille et al, 2017;Rabadi and Rabadi, 2020). Meanwhile, individual differences such as age, gender, and socioeconomic background have been linked to various writing anxiety levels (Huwari and Abd Aziz, 2011).…”
Section: Factors Causing Writing Anxietymentioning
confidence: 99%
“…Writing apprehension is an overwhelming sense of anxiety associated with a feeling of dread when facing a writing activity. The feeling of writing apprehension may develop for numerous reasons including evaluation fear, lack of experience and confidence, or poor writing outcomes in the past (Vanhille, Gregory, & Corser, 2017). Other causes of writing apprehension may stem from a disinterest in writing or having one's work available for public review (Autman & Kelly, 2017).…”
Section: Writing Apprehensionmentioning
confidence: 99%
“…When applied to writing, those who believe they possess the abilities to write well will write effectively, and those who believe they lack the abilities to write well will struggle. Bandura also later theorized that an individual's self‐efficacy comes from four major areas: mastery experiences, where an individual experiences success; vicarious experiences, where a person witnesses someone else's success; verbal persuasion, where an individual is confident in one's own capabilities; and physiological and affective states, where an individual's mindset and outlook focus on confidence (Bandura, 1997; Vanhille et al, 2017). In linking Bandura's theory to writing apprehension, writers with a low self‐efficacy would question their ability to write, would lack experience, lack mentors in writing, and view writing as a stressor, ultimately generating obstacles in writing success.…”
Section: Writing Apprehensionmentioning
confidence: 99%
“…To meet this need, the present study attempts to investigate the effect of online debate in developing argumentative writing and reducing writing apprehension. limited experience and self-confidence , or a history of poor writing results (Vanhille, Gregory, & Corser, 2017). Other reasons for writing apprehension include a dislike of writing or making one's work liable to evaluation (Autman & Kelly, 2017).…”
Section: Introductionmentioning
confidence: 99%